Maxillary reconstruction - Brown James (Indian Journal of Plastic Surgery)
This article aims to discuss the various defects that occur with maxillectomy with a full review of the literature and discussion of the advantages and disadvantages of the various techniques described. Reconstruction of the maxilla can be relatively simple for the standard low maxillectomy that does not involve the orbital floor (Class 2). In this situation the structure of the face is less damaged and the there are multiple reconstructive options for the restoration of the maxilla and dental alveolus. If the maxillectomy includes the orbit (Class 4) then problems involving the eye (enopthalmos, orbital dystopia, ectropion and diplopia) are avoided which simplifies the reconstruction. Most controversy is associated with the maxillectomy that involves the orbital floor and dental alveolus (Class 3). A case is made for the use of the iliac crest with internal oblique as an ideal option but there are other methods, which may provide a similar result. A multidisciplinary approach to these patients is emphasised which should include a prosthodontist with a special expertise for these defects.